Effect of Steaming on the Colorimetric Properties of Eucalyptus saligna Wood - Reinaldo Calçada Guina Luís; Silvana Nisgoski; Ricardo Jorge Klitzke (Floresta e Ambiente, 2018)
ABSTRACT This study aimed to homogenize the color of Eucalyptus saligna wood by means of steaming and compare the resulting color with that of Cariniana legalis wood, a species of high commercial value. To this end, two steaming curves were tested: 100% relative humidity for 12 (T1) and 24 (T2) hours at 90 °C followed by drying in a pilot-scale conventional kiln. The colorimetric parameters L*, a*, b*, C*, and h were determined according to the CIE L*a*b* color measurement system after drying. Results showed that steaming can be used for color homogenization between heartwood and sapwood. The treatment conducted for 24 hours (T2) presented the best results.